ARTIFICIAL INTELLIGENCE, GENOM, CYBERSPACE AND SPACE – CONTEMPORARY THREATS TO THE SECURITY OF THE STATE AND NATIONS - Jan A. WENDT (Revista Română de Geografie Politică, 2023)
Among many contemporary threats, which include threats in the military, economic or social sphere, issues related to threats in cyberspace, artificial intelligence (AI), genetic modifications of the human genome and threats related to with space exploration. This work, based on a qualitative analysis of the literature, aims to identify selected, often overlooked and not functioning in the common awareness of contemporary threats to state security. The analysis undertaken allows us to conclude that an important factor contributing to the increase in the level of threat to the security of the state and nation today are the contemporary "black swans" in the security sphere, the weakness of political leadership, unknown directions of AI development and changes in the human genome, threats related to the outer space exploration and threats in cyberspace.